125 Galveston County Youth Risk Survey: A Glimpse into Our Children's Health and Wellbeing. (April 2022) - Bohn, Krista; Croisant, Sharon; Singleton, Chantele; Prochaska, John; Hallberg, Lance
Abstract : OBJECTIVES/GOALS: The 2020-2021 Galveston County Youth Risk Survey continues past efforts to characterize behavioral risks for local youth, identify disproportionate risks among groups, and provide the data needed for action and intervention to improve the health and safety of our youth in Galveston, Texas. METHODS/STUDY POPULATION: While the survey is based on the CDC Youth Risk Behavior Surveillance System (YRBSS), there was community need for an expanded survey and thus a workgroup was formed to create the Galveston Youth Risk Survey, including members from UTMBs Institute for Translational Sciences, a number of other UTMB departments and Centers, the Research, Education, and Community Health (REACH) Coalition, several school districts, Teen Health Clinic, and a variety of other community health organizations with vested interest. The survey was administered in November 2020 via ScanTron and REDCap to two local high schools with populations greater than 2, 000. CDC guidelines for administration of the YRBSS were followed. RESULTS/ANTICIPATED RESULTS: A total of 2, 428 students completed the survey from GISD and DISD. The survey provided insight into the following categories, with mental health emerging as a pressing issue, specifically stress and depression, particularly among females. All results are reported in several contexts, including comparisons by gender, grade, and ethnicity, a comparison to state and national statistics when available, as well as risk trends from previous surveys. Demographics Safety, including driving, violence, and bullying Mental Health: stress, depression, suicidal ideation, and ACEs Human Trafficking Substance Use, including smoking, alcohol, marijuana, and other drug use Sexual Behaviors, including contraceptive use Body Weight and Body Image Health Conditions Home Life: Support and Security DISCUSSION/SIGNIFICANCE: The report has been presented to the school districts, immediate stakeholders, REACH membership, and the general public. Several presentations have been given to groups to report the findings. Workgroups will now be formed to address the needs of our students, as well as a possible follow-up survey to look at data specific to COVID-19 and mental health.